Keanekaragaman Jenis Kantong Semar (Nepenthes spp.) di Kawasan Taman Wisata Alam Baning Kabupaten Sintang Kalimantan Barat - Mukarlina, Anggi Nurhadi Riza Linda (Jurnal Protobiont, 2018)
Baning Natural Tourism Site located in Sintang district is the habitat of Nepenthes spp. The aim of the study is to determine the spesies and diversity of Nepenthes spp. in Baning Tourism site. The study was conducted in April - May 2017.Â  Nepenthes spp. observation was done in 5 observation locations which was determined randomly based on the homogeneity of Nepenthes in Baning site with the total number of the observation area of 0.096 Ha. The results showed that there are 5 spesies of Nepenthes in Baning namely Nepenthes ampullaria, N. bicalcarata, N. mirabilis, N. gracilis, and N. x cantleyi. The diversity of Nepenthes spesies in Baning observation areas is to low, with the value of H' ranging from 1,075 to 0.616.